2020
DOI: 10.1111/jce.14835
|View full text |Cite
|
Sign up to set email alerts
|

A simple pacing maneuver to unmask an epicardial connection involving the right‐sided pulmonary veins

Abstract: Introduction An epicardial connection (EC) between the right‐sided pulmonary venous (PV) carina and right atrium (RA) is one of the mechanisms for which carinal ablation is required for right‐sided PV isolation. The purpose of the study was to devise a simple pacing maneuver to differentiate an EC from a residual conduction gap on the antral ablation line during radiofrequency catheter ablation. Methods and Results This study included 133 consecutive patients. After one round of ablation, electrograms at the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Recent studies have suggested the presence of an epicardial connection involving the PVs as one of the mechanisms for failure of isolation by circumferential lesion sets. 1 , 2 , 3 , 4
Learning Objectives
To recognize the presence of epicardial connections as a possible cause of failure of first-pass isolation. To recognize an epicardial connection between the pulmonary veins and the left atrium in addition to Marshall bundle and coronary sinus musculature.
…”
mentioning
confidence: 99%
“…Recent studies have suggested the presence of an epicardial connection involving the PVs as one of the mechanisms for failure of isolation by circumferential lesion sets. 1 , 2 , 3 , 4
Learning Objectives
To recognize the presence of epicardial connections as a possible cause of failure of first-pass isolation. To recognize an epicardial connection between the pulmonary veins and the left atrium in addition to Marshall bundle and coronary sinus musculature.
…”
mentioning
confidence: 99%
“…A wide area circumferential ablation (WACA) at the antrum has increasingly replaced the pulmonary vein (PV) ostial ablation because of a higher success rate and reduced risk of PV stenosis 1 . However, epicardial connections with intercaval fibers between the right atrium (RA) and right pulmonary vein (RPV) can bridge the WACA lesions, which could lead to a challenging RPV antral ipsilateral isolation only with a continuous linear ablation encircling the RPV 2,3 …”
Section: Figurementioning
confidence: 99%
“…The earliest activation was observed at the anterior RIPV inside the WACA, which was identical to the LA breakthrough during RA pacing distant from the WACA line (Figure 2A,C). Pacing maneuvers 2 to differentiate epicardial connections from gaps on the WACA line (The Δinterval SR‐CS at posterior antrum was 94 ms), suggested there was an epicardial connection. Once the RPV was isolated by an RF application at that epicardial connection (Epi‐connection 2 in Figure 1), an acute reconnection occurred again (the earliest activation was found on the anterior carina [Epi‐connection 1 in Figure 1], which was the LA breakthrough site during sinus rhythm far from the WACA line; Figure 2B,D).…”
Section: Figurementioning
confidence: 99%
“…Spontaneous recovery of the PQ interval was noted after cardioversion. Although PV potentials were found in the RtPV carina, gap conduction was unlikely, on the basis of careful PV antral mapping and the pacing study ( 8 ). Thus, we decided to create an activation map of the RA during pacing from a LASSO catheter (Biosense Webster, Inc.) placed in the right superior PV ( 5 , 8 ).…”
Section: Managementmentioning
confidence: 99%
“…Although PV potentials were found in the RtPV carina, gap conduction was unlikely, on the basis of careful PV antral mapping and the pacing study ( 8 ). Thus, we decided to create an activation map of the RA during pacing from a LASSO catheter (Biosense Webster, Inc.) placed in the right superior PV ( 5 , 8 ). The earliest activation site was found in the right atrial posteroseptal wall ( Figure 2A ), and ablation of that site achieved RtPV isolation ( Figure 2B ).…”
Section: Managementmentioning
confidence: 99%